Pengembangan Asesmen Guru Biologi dalam Merancang Perangkat Pembelajaran Berbasis Kompetensi Pedagogik dan Profesional : (Development of assessment of biology teachers in designing learning tools based on pedagogic and professional competencies) - Meri Suryani; Bambang Hariyadi; Yusnaidar Yusnaidar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to determine the development of the assessment instrument for biology teachers in designing learning tools based on pedagogic and professional competencies and the principal's perception of the assessment instruments that have been developed. The type of research used is instrument development research from the ADDIE model, this model has 5 stages, namely: analysis, design, development, implementation and evaluation. Instrument products before being tested are validated, product validation is carried out by material experts and design experts. Material expert validation got a score of 92% in the